Prototype of Voltage, Current, Temperature, and Oil Level Monitoring System in Transformers - Alfonsus Bramasadewa Putra; Usman Nursusanto (Journal of Robotics, Automation, and Electronics Engineering, 2024)
A distribution transformer is the most crucial component of the electric power distribution system. The output values of parameters such as voltage, current, temperature, and oil level vary, necessitating monitoring. This final project aims to design and build, determine the functional testing of the device, and assess the performance accuracy of its components. The system design results show that the components used in the prototype system are the INA219, AHT10, and HC-SR04 sensors. The measurement results from the sensors are displayed on an Android application and stored in a logger. Functional test results indicate that all components used in the prototype monitoring system function normally, and the measurement errors are within the datasheet limits of each component. The percentage error values from the accuracy testing of the sensors show values below 5%, with the largest error being 3.2% in current measurement and the smallest error being 0.0% in distance measurement. Therefore, the sensors are in good condition, and these values are below the IEC 13B-23 standard limits.